Maraval Reservoir, Trinidad. - (:unkn) unknown (Wilson Ltd., Trinidad, 2010)
Image depicts a view of the Maraval Reservoir, located in the town of Maraval on the island of Trinidad in the Republic of Trinidad and Tobago.
Colour: Shades of Green, Red, Brown, Blue and Gray; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Maraval; Reservoirs--Trinidad and Tobago; Architecture--Trinidad and Tobago